Analysis of Pedagogical Integration in natural Science Distance Learning System - A. A. Ketut Budiastra; Kadarisman Kadarisman; Iwan Wicaksono; Nia Erlina; Mudayat (Universitas Muhammadiyah Enrekang, 2026)
This research aims to analyze the implementation of integrating content, media, and teaching methods as learning outcomes in natural science learning. The context of carrying out this research is a distance learning system. This descriptive research focuses on pedagogical competence, graduate opinion, supporting factors, and obstacles faced in integrating content, media, and teaching methods. The research participants were 94 teachers from various islands who taught in grades 4, 5, and 6. The stages for obtaining data began with distributing responses, teaching observations, natural science content tests, and interviews with several teachers as representatives. This research shows that teachers have achieved high success in several aspects of natural science learning based on data analysis, including initial motivation, the relationship of material to daily life, and material explanations, reaching more than 85%. The results of the interviews show that variations in approaches and obstacles related to the completeness of natural science technology instrument facilities need more attention to improving facilities and teacher understanding. Data analysis shows good achievement with potential for improvement, particularly in demonstrations, teaching methods, and integration of natural science content. Observations of teacher activities provide positive picture, while teachers' opinions regarding the student-centered approach show creativity in overcoming facility constraints. Thus, increasing accessibility to technology and digital learning resources can help overcome obstacles in integrating content, media, and teaching methods in natural science learning. The results of this research provide important insights for developing strategies and policies to increase the effectiveness of natural science learning in distance learning systems.